Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The extent of Appropriateness of the school environment within Nablus Directorate for development of talented students at Lower Basic Schools from their teachers' point of viewMrs. Fayha Abd Al-Salam Sholi2. The reality of human resource training in the Directorate of Education in the Governorate of Al-Wusta in the Sultanate of Oman from the perspective of employeesMr. Mansoor Abdullah Salim Al-Junaibi3. A proposed scenario for the partnership between Ministry of Education and the third sector  in training secondary school teachers on skills the twenty-first century in the light of global experiencesMr. Mashael Abdullah Ayed Al-Qahtani4. Evaluation of blended learning during Corona pandemic from the point of view of teachers  and principals of public schools in Jerusalem governorateMrs. Iman Ali Obaydieh\ Inairat, Dr. Kifah Ahmad Barham5. Visual Thinking as a Predictor of Cognitive curiosity in Early Childhood Stage in Taif GovernorateCo-Prof. Khawlah Jamil Al-Ansari, Mrs. Najlaa Attyah Al-Juaid
Keywords: Journal of Educational and Psychological Sciences